(untitled) (Pedagogy of Higher and Secondary Education, 2006)
In clauses articles) the problem of professional independence of students - the future teachers of an artwork in works of known teachers is examined: V. Suhomlinskogo, V. Kozakova, A. Makarenko, V. Bezpalka and others.